(untitled) (Boletin Médico de Postgrado, 2024)
A brief tour of the history of gastroenterology is made, from the papyrus of Ebers, Hippocrates, Avicenna and Galen, passing through Vesalius, Glisson, Peyer, Lieberkühn, Sylvius and Spallanzani, to reach William Beaumont, the father of gastroenterology; Philipp Bozzini, the creator of the first endoscope; Désormeaux who coined the term “endoscope”; Ismar Boas, the first licensed doctor and an exclusive clinic for gastrointestinal diseases (first gastroenterologist and first professor of gastroenterology), Iván Pavlov and Robin Warren/Barry Marshall who would be Nobel Prize winners in Medicine and finally, the founders in Venezuela, such as Carlos Ottolina and Valencia Parparcén (among others), all excellent doctors, academics and researchers, who fought against the adversities of any beginning, overcoming obstacles and achieving successes that, over the years, are multiplied in their fruits, in this beautiful specialty that has saved thousands of lives and continues to be full of good people willing to help those most in need, this simple historical recognition goes to all of them.